Why Do K-Pop Fans Buy Impulsively? A Study on Perceived Scarcity, FOMO, and Self-Control - Sharon Rivani Martiza; Effed Darta Hadi (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: The development of Korean pop culture (K-pop) has become a global phenomenon that permeates various aspects of life, including Indonesia. Its success extends beyond the entertainment sector, significantly influencing the lifestyle and consumption behaviour of its enthusiasts. Many fans are not only passionate about their idols' music and performances but also tend to purchase merchandise impulsively. Purpose: This study aims to examine the impact of perceived scarcity on impulsive buying behaviours for K-Pop merchandise, by exploring the mediating role of FOMO and the moderating effect of self-control. Method: Using a quantitative approach, data were collected through an online survey of 358 K-pop fans in Indonesia, selected via purposive sampling, and analysed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Findings: The findings indicate that perceived scarcity has a positive and significant influence on FOMO, which in turn enhances impulsive buying behaviour. However, perceived scarcity does not directly affect impulsive buying without the mediating role of FOMO. Moreover, self-control significantly moderates the relationship between FOMO and impulsive buying by weakening the effect, indicating that individuals with greater self-control are less likely to engage in impulsive purchases despite experiencing FOMO. Conclusions: This research highlights the significant influence of FOMO on impulsive buying behaviour among K-Pop fans, particularly in the context of scarcity-based marketing. In contrast, self-control functions as a mitigating factor. Research implication: The findings provide valuable insights for marketers to implement ethical scarcity-based strategies while encouraging responsible consumer behaviour among K-Pop fans.